Clinically Undetected Hodgkin Lymphoma Diagnosed Initially on Bone Marrow Biopsy: A Large Retrospective Observational Study from a Tertiary Care Center - Vangala, Navatha; Paul, Tara Roshni; Uppin, Shantveer G.; Uppin, Megha S.; Sadashivudu, G.; Raju, Y. Satyanarayana; Rao, M. Nageswara (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Hodgkin lymphoma (HL) involving the bone marrow (BM) is relatively rare with an incidence ranging from 4% to 18%. The incidence of primary HL of marrow is 0.25%. To the best of our knowledge, the present study is the largest study on HL diagnosed initially on marrow biopsy.Objective To establish diagnostic criteria based on clinicopathological and histological features in HL diagnosed first on the marrow.Materials and Methods This was a retrospective study done from January 2012 to December 2020 that included 36 cases of HL diagnosed initially on BM. Based on the presence of large mononuclear or binucleate Reed–Sternberg (RS)-like cells in a polymorphous inflammatory background, HL was suspected and immunohistochemistry (IHC) with CD15 and CD30 was done. Correlation with subsequent lymph node biopsies was done, wherever possible.Results Fever (94.4%) was the most common symptom, followed by loss of weight (66.7%). Twenty-one cases (58.4%) had uni/bicytopenia and 15 cases (41.6%) had pancytopenia. Only one case showed suspicious mononuclear RS cells on aspirates and the rest of the cases were diagnosed on trephine biopsy alone. Trephine imprints showed variable cellularity in 13 (36%) cases. Diffuse involvement was seen in 24 cases (66.7%), and focal nodular aggregates were seen in 12 cases (33.3%). Out of 36 cases, 26 cases (19 cases on marrow and 7 cases on lymph node) were confirmed as HL with IHC. Immunophenotype of the RS cells on the marrow was CD30+/CD15+ in (6/29) (20.7%) cases, CD30+/CD15− in (7/29) (24.1%) cases and CD30−/CD15+ in (6/29) (20.7%) cases. Seven cases (26.9%) were diagnosed on subsequent lymph node biopsy as mixed cellularity HL with IHC confirmation. Marrow fibrosis was seen in 16 cases (44.4%), and granulomas were seen in 8 cases (22.2%).Conclusion In cases presenting with long-standing fever and cytopenias, HL must always be suspected, even if there are no palpable lymph nodes. Bone marrow biopsy is preferable over aspiration in such cases and IHC plays a major role in diagnosing the cases.
Keywords: Hodgkin lymphoma; primary diagnosis; bone marrow biopsy